A pre-investigational new drug study of lung spheroid cell therapy for treating pulmonary fibrosis. (18th April 2020) - Cores, Jhon; Dinh, Phuong-Uyen C.; Hensley, Taylor; Adler, Kenneth B.; Lobo, Leonard J.; Cheng, Ke
Abstract: Idiopathic pulmonary fibrosis is a lethal interstitial lung disease with unknown etiology, no cure, and few treatment options. Herein, a therapy option is presented that makes use of a heterogeneous population of lung cells, including progenitor cells and supporting cells lines, cultured in adherent and suspension conditions, the latter of which induces spontaneous spheroid formation. Within these spheroids, progenitor marker expression is augmented. The cells, called lung spheroid cells, are isolated from fibrotic lungs, expanded, and delivered in single cell suspensions into rat models of pulmonary fibrosis via tail-vein injections. Two bleomycin-induced fibrotic rat models are used; a syngeneic Wistar-Kyoto rat model, treated with syngeneic cells, and a xenogeneic nude rat model, treated with human cells. The first objective was to study the differences in fibrotic progression in the two rat models after bleomycin injury. Nude rat fibrosis formed quickly and extended for 30 days with no self-resolution. Wistar-Kyoto rat fibrosis was more gradual and began to decrease in severity between days 14 and 30. The second goal was to find the minimum effective dose of cells that demonstrated safe and effective therapeutic value. The resultant minimum effective therapeutic dose, acquired from the nude rat model, was 3 × 10 6 human cells. Histological analysis revealed no evidence of tumorigenicity, increased local immunological activity in the lungs, or an increase in liver enzyme production. These data demonstrate the safety and efficacy of lung spheroid cells in their application as therapeutic agents for pulmonary fibrosis, as well as their potential for clinical translation. : Abstract : Lung spheroid cells are a cellular therapeutic achieved after a sequential 2D-3D-2D culture regiment. The steps include acquiring transbronchial biopsies from human idiopathic pulmonary fibrosis (IPF) patients, allowing the cells to migrate out of the biopsy, creating spheres from the migrated cells in suspension culture, and replating the spheres, which adhere and separate into individual LSCs.